(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The term "cyber physical system" (CPS) refers to the increasingly common practise of embedding internet connectivity and sensing/transmitting capabilities into everyday things. Think about a smart home app that uses CPS gadgets. Due to its many benefits, such as saving time and money and improving human comfort and energy efficiency, the IoT has been more popular in recent years. The cyber physical system relies heavily on the low-capacity sensor node. To function as clients or hosts on the internet, these diverse components communicate with one another across a wireless network. Due to resource limits including little storage capacity, restricted computing power, and limited energy backup, the well-known security methods employed in desktop computers cannot function on these systems. SecureAuthKey is a lightweight authentication and key agreement system. Security and privacy concerns in existing constraint-based CPS applications are the focus of the proposed method. The final product is supposed to be a simple method of authenticating cyber-physical systems. Trustworthy, private, and data-protecting security algorithm for cyber-physical systems that does not compromise their ability to learn and act autonomously